Hydrothermal oxidative valorisation of lignin into functional chemicals: A review. (December 2021) - Kumar, Avnish; Biswas, Bijoy; Kaur, Ramandeep; Krishna, Bhavya B; Bhaskar, Thallada
Highlights: Innovative presentation of lignin structure and its breakdown mechanism. Detailed discussions on reaction conditions that promote oxidative depolymerization. Mechanistic pathways of decomposition using oxidizing agents explained. Heterogeneous catalysis helps in improving selectivity towards functional chemicals. Abstract: Lignin is a waste by-product of bio-refineries and paper-pulp industries. It has an attractive potential to produce numerous valuable chemicals due to its highly aromatic character. At present, large amount of lignin is burnt as a source of energy due to lack of suitable efficient lignin valorisation processes. The challenge exists in handling its complex heterogeneous structure and bond breaking at selective locations. The production of high value chemicals/petrochemical feedstocks will improve the economic viability of a bio-refinery. Oxidative depolymerization is a promising way to produce functional compounds from lignin. The aim of the current review is to present the novel methodologies currently used in the area of lignin oxidative depolymerization including effect of temperature, residence time, solvent, oxidizing agents, homogeneous and heterogeneous catalysis etc. It aims to present an insight into the structure of lignin and its breakdown mechanism.